A Rare Case of Extensive Cerebral Venous Sinus Thrombosis Complicated by Heparin-Induced Thrombocytopenia - Jang Khan, Noman Ahmed; Farooqi, Ashar; Alsharedi, Mohamed (Case Reports in Hematology, 2022)
Cerebral venous sinus thrombosis (CVST) is a rare but potentially life-threatening cause of stroke. Several risk factors have been identified including hypercoagulable state, malignancy, use of oral contraceptives, pregnancy, head injury, infection, and prothrombotic states such as heparin-induced thrombocytopenia (HIT). HIT is a prothrombotic state leading to thrombosis in several distinct locations including CVST requiring prompt discontinuation of heparin and initiation of nonheparin anticoagulation to prevent catastrophic consequences. Very rarely, HIT can complicate the ongoing CVST leading to worsening thrombosis and clinical deterioration. We here report an exceedingly rare case of CVST complicated by HIT in a 22-year-old female patient who showed remarkable clinical improvement after discontinuation of heparin and initiation of argatroban.